The Challenges of Virtual Learning Environment in Mathematics in the Context of Nepal: no subtitle (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
The aim of this study was to identify the challenges faced by the learners in virtual learning in mathematics. A qualitative case study was conducted in Mid-western University, Nepal. Altogether ten participants from different districts of Karnali Province were chosen purposively. In-depth interviews and focus group discussions were the tools of data collection. Collected data were transcribed, coded and categorized to develop themes. The method of data analysis is thematic with quotations and block quotes. The study revealed that virtual learning is an opportunity in higher education for job holders and married women as well as others who could not join face to face classes, although it has many challenges. The finding indicates that the learners have faced pedagogical challenges, technological challenges, challenges of time management, environmental challenges and psychological challenges.